Pengaruh Transparansi dan Akuntabilitas Pengelolaan Dana Zakat Terhadap Kepercayaan Muzzaki dalam Membayar Zakat di Baznas Provinsi Jawa Barat - Nasution, Ade Iskandar; Hermawati, Natasya Nur; Rahmat Setia, Mochamad Nur (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Based on the results of observations as the background of this research, is the effect of transparency and accountability in the management of zakat funds on muzzaki's trust in paying zakat at Baznas West Java Province which causes fluctuations in the number of muzzaki, the number of planned realization of zis recipients each year.This study aims to determine how the effect of transparency and accountability in the management of zakat funds on muzzaki's trust in paying zakat at the Baznas of West Java Province, both partially and simultaneously. The object of research in this report is to measure muzzaki's trust. The type of research is quantitative associative with primary data types and uses data collection techniques in the form of observation, interviews, literature studies, and questionnaires. Sampling data collection uses saturated sampling. The population is muzzaki or people who pay zakat in Baznas, West Java Province. The results of this study indicate that there is a significant effect between transparency on muzzaki's trust by testing the results of the hypothesis that tcount > ttable (6.759> 1.290), there is a significant influence between accountability of zakat fund management on muzzaki's trust resulting from the t test (8.835>1.190), simultaneously there is a significant influence between the value of transparency and accountability of zakat fund management Fcount > Ftable 570,522 > Ftable 1,070 with a significant level of 0.000 <0.1.